A photo-responsive bifunctional electrocatalyst for oxygen reduction and evolution reactions. (January 2018) - Lv, Jiangquan; Abbas, Syed Comail; Huang, Yiyin; Liu, Qin; Wu, Maoxiang; Wang, Yaobing; Dai, Liming
Abstract: Oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are of paramount importance towards to regenerative fuel cells and rechargeable metal-air batteries. Many efforts have been devoted to developing high active ORR and OER bifunctional electrocatalysts to improve the efficiency of devices. However, the possibility of using free solar energy in ORR/OER electrocatalysts to get higher efficiency in the devices has not yet been recognized. Herein, we report a photo-responsive bifunctional ORR/OER electrocatalyst with a built-in p-n heterojunction based on Ni12 P5 nanoparticles (NPs) coupled strongly with nitrogen-doped carbon nanotubes (NCNT). The Ni12 P5 @NCNT hybrid catalyst exhibited unusually high catalytic activities for both ORR (onset potential at 0.90 V vs. RHE) and OER (η = 360 mV @10 mA cm −2 ) in 0.1 M KOH solution with a ΔE (E OER j = 10 - E ORR 1/2 ) = 0.82 V, comparable to that of its state-of-the-art counterparts (e.g., Pt for ORR, IrO2 for OER). Upon light irradiation (300 W Xenon lamp equipped with an AM 1.5G filter, 5 cm to electrode), the ΔE further decreased to 0.80 V. A rechargeable Zn-air battery devised from a Ni12 P5 @NCNT cathode in 6 M KOH/0.2 M Zn(Ac)2 exhibited a low charge-discharge voltage gap ( 0.75 V @ 10 mA cm −2, charge potential = 1.94 V and discharge potential = 1.19 V) and a remarkable cycling stability over 500 cycles, which, upon the light irradiation, showed an even lower charge potential of 1.90 V and higher discharge potential of 1.22 V (i.e., a charge-discharge voltage gap: 0.68 V @ 10 mA cm −2 ). The irradiation caused also a concomitant increase in the round-trip efficiency from 61.3% to 64.2%. To demonstrate the potential applications in portable/wearable electronic devices, we have also developed all solid-state flexible photo-assisted rechargeable Zn-air batteries based on the Ni12 P5 @NCNT air electrode with high-performance in the both presence and absence of light irradiation. This conceptual demonstration of the first photo-responsive ORR/OER bifunctional catalyst is significant as it reveals a novel catalytic mechanism, from which a class of new bifunctional catalysts with further enhanced photo-responsive performance could be developed, using in other rechargeable metal-air batteries. Graphical abstract: The Ni12 P5 @NCNT hybrid catalyst with both ORR (onset potential at 0.90 V vs. RHE) and OER (η = 360 mV @10 mA cm −2 ) activity in 0.1 M KOH solution was equipped as the cathode in a rechargeable Zn-air battery, which exhibited a low charge-discharge voltage gap ( 0.75 V @ 10 mA cm −2) and further decrease to 0.68 V under light irradiation. The irradiation caused extremely high the round-trip efficiency of 64.2%. Highlights: We developed a photo-responsive bifunctional catalyst using in Zn-air batteries. The photo-assisted Zn-air battery showed high round-trip efficiency of 64.2%. We made flexible photo-assisted Zn-dair batteries for wearable optoelectronic devices.